Gender Differences in Smoking Among U.S. Working Adults - Syamlal, Girija (Am J Prev Med, 2014)
BACKGROUND: Cigarette smoking remains a leading cause of morbidity and mortality. Although gender differences in cigarette smoking in the U.S. population have been documented, information on these differences among working adults is limited. PURPOSE: To describe the current smoking prevalence by gender among working U.S. adults and examine gender differences in smoking by occupation. METHODS: The 2004–2011 National Health Interview Survey data for adults aged ≥18 years that were working in the week prior to the interview (N=132,215) were analyzed in 2013. Current cigarette smokers were those who smoked at least 100 cigarettes in their lifetime and currently smoke every day or some days. RESULTS: During 2004–2011, an estimated 22.8% of men workers and 18.3% of women workers were current smokers. Of the current smokers, women workers had higher odds of being an everyday smoker (prevalence OR [POR]=1.17, 95% CI=1.09, 1.26); having poor self-rated emotional health (POR=1.28, 95% CI=1.15, 1.41); and having chronic obstructive pulmonary disease (POR=2.45, 95% CI=2.14, 2.80), heart disease (POR=1.27, 95% CI=1.12, 1.45), and current asthma (POR=2.21, 95% CI=1.96, 2.49) compared with men workers. Women in “supervisors, construction, and extraction” (38.9%) occupations and men in “extraction” (40.5%) occupations had the highest smoking prevalence. CONCLUSION: Among working adults, women had lower prevalence of smoking than men, yet women who smoke were more likely than men to have adverse health outcomes, including self-rated poorer physical and emotional health.